The bacterial community and metabolome dynamics and their interactions modulate fermentation process of whole crop corn silage prepared with or without inoculants. Issue 2 (6th July 2020) - Xu, Dongmei; Wang, Nian; Rinne, Marketta; Ke, Wencan; Weinberg, Zwika G.; Da, Mi; Bai, Jie; Zhang, Yixin; Li, Fuhou; Guo, Xusheng
Summary: Multi‐omics approach was adopted to investigate the modulation of bacterial microbiota and metabolome as well as their interactions in whole crop corn ensiling systems by inoculating homofermentative Lactobacillus plantarum or heterofermentative Lactobacillus buchneri . Inoculations of the two different inoculants resulted in substantial differences in microbial community and metabolic composition as well as their dynamics in ensiled corn. Inoculants also altered the correlations of microbiota in different manners, and various keystone species were identified in corn silages with different treatments. Many metabolites with biofunctional activities like bacteriostatic, antioxidant, central nervous system inhibitory and anti‐inflammatory were found in the present silage. A constitutive difference in microbiota dynamics was found for several pathways, which were upregulated by specific taxa in middle stage of fermentation, and widespread associations between metabolites with biofunctions and the species of lactic acid bacteria dominated in silage were observed. Multiple microbial and metabolic structures and dynamics were correlated and affected the fermentation process of the corn ensiling systems. Results of the current study improve our understanding of the complicated biological process underlying silage fermentation and provide a framework to re‐evaluate silages with biofunctions, which may contribute to target‐based regulation methods to produce functional silage for animal production. Abstract : Multi‐omics approach was adopted to investigate the modulation of bacterial microbiota and metabolome as well as their interactions in whole crop corn ensiling systems by inoculating homofermentative Lactobacillus plantarum or heterofermentative Lactobacillus buchneri . Results of the current study improve our understanding of the complicated biological process underlying silage fermentation, and provides a framework to re‐evaluate silages with biofunctions, which may contribute to target‐based reglation methods to produce functional silage for animal production.